Attenuation of Acute Renal Injury After the Post-resuscitation Administration of Doxycycline in Surviving Newborn Piglets With Severe Hypoxia-Reoxygenation - Lee, Tze-Fun; Lu, Min; Pasquin, Matteo P.; Schmölzer, Georg M.; Cheung, Po-Yin (Frontiers in Pediatrics, 2019)
Background: Asphyxiated neonates often have myocardial dysfunction and renal insufficiency. Previously we demonstrated that doxycycline improved cardio-renal function through matrix metalloproteinase (MMP)-2 inhibition in an acute swine model of neonatal hypoxia-reoxygenation. The prolonged cardio-renal protective effects of doxycycline in neonates still remained unknown. We therefore hypothesized that the protective effects of doxycycline persisted in surviving subjects. Methods: Newborn piglets were instrumented and subjected to 1 hour of hypoxia followed by reoxygenation with 21-25% oxygen and observed for 4 days. Intravenous doxycycline (30 mg/kg) or normal saline (1 mL, saline-control group) was given at 5 minutes of reoxygenation (n=8/group) in a randomized, blinded fashion. Sham-operated piglets (n=5) received no hypoxia-reoxygenation. At 96 hours after reoxygenation, the left ventricular function was assessed by Millar® catheter. Renal injury was investigated by measuring plasma creatinine, urinary N-acetyl-D-glucosaminidase activity, renal tissue lactate and MMP-2 activity. Results: Both hypoxia-reoxygenation groups had similar hypoxic stress with severe lactate acidosis, and hemodynamic recovery. Doxycycline-treated piglets had higher urine output with lower urine N-acetyl-D-glucosaminidase, plasma creatinine and renal MMP-2 activity (vs. saline-controls; all p<0.05). These markers were all negatively correlated with urine output. Conclusions: In newborn piglets surviving hypoxia-reoxygenation, we observed a weak but significant and persistent attenuation of renal injury and improved recovery with the post-resuscitation administration of doxycycline.